Historical dictionary of Marxism - Walker, David M. (David Martin), 1963- (Historical dictionaries of religions, philosophies, and movements., 2014)
The second edition of Historical Dictionary of Marxism covers the basics of Karl Marx's thought, the philosophical contributions of later Marxist theorists, and the extensive real-world political organizations and structures his work inspired--the myriad political parties, organizations, countries, and leaders who have subscribed to Marxism as a creed. This book includes a chronology, an introduction, and an extensive bibliography. The dictionary section contains more than 500 cross-referenced entries on important personalities, both thinkers and doers; political parties and movements; and major communist or ex-communist countries. It is an excellent reference for students, researchers, and anyone wanting to know more about Marxism.